Structure and process of nursing care for prevention of surgical site infection: observational study - Lucia Marta Giunta da Silva; Larissa Christiane Pawluk; Luiz Henrique Gebrim; Gil Facina; Maria Gaby Rivero de Gutiérrez (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
High rates of infection can reflect the quality of the service. Two previous studies in the same place reported an overall surgical site infection incidence of 14,1% and 22%, what motivated this research.  The aim of this study was to analyze the structure and nursing process and its possible relationship with the prevention and control of surgical site infection (SSI). It is a descriptive, observational and documentary analysis study performed in a large general teaching Hospital in São Paulo from August 2007 to March 2008. The data were collected from institutional documents and trough directed observation of the nursing practice. The results showed that the normative documents are in accord with the current evidence. However, the structure issues present limitations with negative impact for the prevention of SSI. The nursing processes accomplished partially to the recommended standards, the hand washing, appropriate use of antibiotics and accomplishment of postoperative dressing's present improvement opportunities that could positively impact the surgical site infection's rates. These results point out the need of review the nursing process and the adequacy of some structural issues in order to achieve the standards for prevention and control of the surgical site infection.